Marine biodiversity in the dark: an ecological assessment of a unique submerged cave system in the eastern Mediterranean Sea - VASILIS RESAIKOS; STELIOS KATSANEVAKIS; MARIOS PAPAGEORGIOU; GEORGIOS OIKONOMIDIS; CARLOS JIMENEZ (Mediterranean Marine Science, 2026)
Submerged caves in the Mediterranean Sea are unique ecosystems, sustaining diverse benthic communities shaped by environmental gradients. This study focused on the Jubilee Shoals cave system in the eastern Mediterranean (Cyprus), providing a quantitative analysis of benthic community composition, spatial distribution across cave zones, and the influence of environmental factors. The data were collected using closed-circuit rebreathers; 341 photo quadrats were analysed with specialised software to assess biodiversity within this cave system. Overall, 59 sessile taxa were identified at different rank, with sponges comprising 33% of richness. Phototrophic species dominated the entrance zone, while sponges and other low-light-adapted organisms prevailed in the darker areas. Light availability significantly influenced community structure. A progressive decline in biotic coverage from entrance to dark zones and an increase in non-living substrates highlighted the environmental limitations of more remote cave sections. Detailed 2-D and 3-D mapping enhanced our understanding of the structural complexity of the cave and species distribution. These findings emphasise the ecological vulnerability of sea caves and highlight the need for focused conservation efforts. This study establishes a foundation for future ecological studies in deep marine cave systems.

Describing Dolphin Interactions with Cypriot Fisheries Using Fishers’ Knowledge - Marios Papageorgiou; Soteria-Irene Hadjieftychiou; Chistodoulos Christodoulou; Antonis Petrou; Dimitrios K. Moutopoulos (Journal of Marine Science and Engineering, 2024)
The study explores the interactions between dolphins and Cypriot fisheries, emphasizing the economic impact and fisher perceptions through data collected from structured interviews with small-scale and large pelagic fishers. The research documents frequent dolphin interactions, impacting catch and gear in both fishing sectors. Reported financial losses and gear damage highlight a significant economic burden, with annual losses averaging EUR 6144 for small-scale and EUR 29,882 for large pelagic fishers. Efforts to mitigate these interactions, such as using acoustic deterrents, have shown mixed results, reflecting dolphins’ adaptability to human activity. While some fishers use deterrents, others remain hesitant due to cost and inconsistent efficacy. The study underscores the need for improved, sustainable solutions that integrate fisher input to enhance acceptance and effectiveness. Findings suggest that dolphins are increasingly relying on fishing activities as a foraging strategy, aligning with broader trends in the Mediterranean. In the context of EU Directive 2014/89/EU, the study integrates ecological considerations and socioeconomic impacts to ensure balanced marine management strategies. This work emphasizes the complexity of human–wildlife conflicts in marine environments, suggesting that further research and collaboration with fishers are essential to developing adaptive strategies that balance conservation with the economic needs of local fishing communities.

Profiling the Cypriot Fisheries Sector through the Lens of Fishers: A Participatory Approach between Fishers and Scientists - Marios Papageorgiou; Christiana Tourapi; Georgios Nikolaidis; Antonis Petrou; Dimitrios K. Moutopoulos (Fishes, 2024)
Despite the sector’s minor contribution (0.5%) to the Gross National Product, the fisheries sector in Cyprus is particularly important to the micro economy of coastal communities, offering direct and indirect employment and supporting small family businesses. Like any industry, the Cypriot fisheries sector faces its own challenges and opportunities. The current study aimed to identify the strengths, weaknesses, opportunities, and threats (SWOT) of the fisheries sector in Cyprus based on fishers’ knowledge and to provide strategic recommendations based on the sector’s identified needs. Following a participatory approach, a workshop with 30 small-scale fishers, six large pelagic longline fishers, and three scientists was conducted in November 2023. Fishers and scientists worked together to conduct the SWOT and the TOWS matrix (a reverse SWOT) analyses. Findings from the SWOT–TOWS analyses were used to develop strategic recommendations for the sector. Finally, using the Impact–Effort prioritisation method, the strategic recommendations were prioritised according to their potential impact on the sector and the effort required for their implementation. Based on the analyses, the study proposes 12 strategic recommendations that could significantly improve the sector’s overall performance and sustainability, which if applied will give a light of hope for the future of the Cypriot fisheries sector.

Small-scale fisheries discards in the eastern Mediterranean Sea: Discarding species, quantities, practices and drivers - Marios Papageorgiou; Dimitrios K. Moutopoulos (Fisheries Research, 2023)

A preliminary assessment of Fistularia petimba (Lacepède, 1803) migration in the Mediterranean Sea: historical and new data from Cyprus (Levantine Sea) with biological notes - MARIOS PAPAGEORGIOU; VASILIS RESAIKOS; ANTONIS PETROU (Mediterranean Marine Science, 2023)
Biological invasions may pose a serious threat to ecosystems and economies. In this study, the presence of the non-indigenous species Fistularia petimba in Cyprus is documented. A total of 76 individuals were collected by bottom trawls and trammel nets in June 2020, March 2021, August 2021, and September 2021. Morphometric measurements, meristic counts, sex, stomach content, and maturity stages were recorded, and notes were made on the length-weight relationship, reproduction, and diet composition. Results from the length-weight relationship indicated a positive allometric growth (b = 3.5127). The preliminary results indicate a prolonged reproductive season, lasting from spring to autumn. The presence of two native and highly commercial fish species, Mullus barbatus and Pagellus sp. in the stomachs of F. petimba highlights the need for further dietary analysis of the species and the study of its impact on local fauna. These findings may confirm the successful establishment of F. petimba in Cyprus and indicate that this species could have similar impacts on local ecosystems as its invasive relative Fistularia commersonii.

Review of catch records of the bigeye thresher shark Alopias superciliosus Lowe, 1841 (Lamniformes: Alopiidae) in the Mediterranean Sea: historical and recent data with biological notes - Vasiliki Kousteni; Vasilis Resaikos; Magdalene Papatheodoulou; Marios Papageorgiou (Journal of Fish Biology, 2022)
In November 2021, a female bigeye thresher shark was incidentally caught by a pelagic drifting longline off southern Cyprus, corresponding to the second documented species record at country level. Main biological features and an extended list of morphometric measurements are presented in comparison with the previous species records in the Mediterranean. The diet analysis highlighted the impact of marine species invasion in the Mediterranean food webs and documented the presence of the angel squid in Cypriot waters for the first time. The species presence in the basin is revised and discussed.

Increased knowledge affects public attitude and perception towards elasmobranchs and support for conservation - MARIOS PAPAGEORGIOU; ELIZABETH BENGIL G.T.; ROBIN SNAPE; LOUIS HADJIOANNOU (Mediterranean Marine Science, 2022)
The tendency of world media to villainize of sharks has likely contributed to a disparity in the distribution of research and conservation resources among threatened marine megavertebrates, with elasmobranchs losing out. Increased public knowledge on elasmobranchs can shape public attitude and foster and gain support for elasmobranch conservation. Through an online survey, this study aimed to evaluate the drivers of public knowledge and examine linkages between awareness of elasmobranchs and attitude toward their conservation. To explore the relationships and effects between the different predicting variables and public elasmobranch knowledge and attitude indices, bi- and multi-variate analysis and a partial least squares path model were used. The results indicated that the average public elasmobranch knowledge of the Cypriot population was moderate and the average public attitude towards elasmobranchs was relatively low. Marine-related activities and marine-related education were highly correlated with increased public elasmobranch knowledge and were the strongest predictors of the partial least squares path model which explained a high degree of variation in elasmobranch knowledge. Public elasmobranch knowledge was highly correlated with public attitude towards elasmobranchs. The findings of this study highlighted the importance of ocean literacy and education and provide insights into the mechanisms for developing and designing successful advocacy actions for elasmobranch conservation.

Understanding the Interactions Between Cetaceans and Other Megafauna With the Albacore Tuna Fishery: A Case Study From the Cyprus’ Pelagic Longline Fishery - Marios Papageorgiou; Louis Hadjioannou; Carlos Jimenez; Andreas Georgiou; Antonis Petrou (Frontiers in Marine Science, 2022)
Depredation by cetaceans on fisheries is a major issue globally, both in terms of conservation and fisheries economics. The present study conducted in Cyprus, Eastern Mediterranean Sea, aimed to understand the extent, level, and type of cetacean depredation on the albacore tuna pelagic longline fishery, and in particular to quantify and evaluate the economic consequences of depredation and identify potential dolphin-longline conflict areas and mitigation practices for management. The data were obtained from fisher’s logbooks, interviews and onboard observations between June and August 2018. A novel and simple approach was applied to estimate the depredation rate and economic loss by using simple calculations including the number and weight of depredated fish, landings and fishing effort. The results revealed that there is an estimated economic loss per fishing trip of 313.07± 486.19 EUR and an estimated annual economic loss for the entire fleet of 259,272 EUR from depredation caused by cetaceans. The study also estimated that 16,639 albacore tunas were depredated in 2018 and the depredation rate ranged between 0% to 100% with a mean depredation rate of 17% per fishing trip. Depredation by the common bottlenose dolphin and striped dolphin was reported in more than 50% of their fishing trips. Other species that were found to be involved in depredation were the neon flying squid, the shortfin mako shark and the Risso’s dolphin. This is the first official record worldwide of depredation from the common bottlenose dolphin, the striped dolphin and the neon flying squid on the pelagic longline albacore tuna fishery. A total bycatch of 62 individuals of common bottlenose dolphins and one individual of stripped dolphin were reported in interviews as a result of depredation on bait and catch. The study also identified depredation hotspots and possible depredation mitigation measures. Such information could support the development of management action plans and measures to minimise interactions between cetaceans and pelagic longlines.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)